Optimisation of the Processes of Written Heritage Preservation and Digitisation - Katuscak, Dusan; Konvit, Martin (Communications - Scientific letters of the University of Zilina, 2013)
The Memory of Slovakia Centre of Excellence (MSCOE) is a project of the University of Zilina, under the scientific and organisational auspices of the Faculty of Humanities implemented from 2010 until 2013. The paper contains information about the project, some outcomes and specialisation of scientific and innovation activities. It describes priorities for research and innovation in the MSCOE, especially optimisation of mass digitisation technology, integrating processes of mass digitisation and conservation of textual materials and optimisation of linguistic solutions in mass digitisation and the best possible preparation of digital content for use.